Social Exclusion Short and Long Term Causes and Consequences - Parodi, Giuliana.; Parodi, Giuliana.; Sciulli, Dario.; Sciulli, Dario. (AIEL Series in Labour Economics,, 2012)
The book provides a panoramic approach to social exclusion, with emphasis on structural causes (education, health, accidents) and on short term causes connected with the crisis which started in 2008. The picture emerging, based on econometric analysis, is that the crisis has widened the risk of social exclusion, from the structural groups, like disabled people and formerly convicted people, to other groups, like the young, unemployed, low skilled workers and immigrants, in terms of income, poverty, health, unemployment, transition between occupational statuses, participation, leading to a widening of socio-economic duality. It has also been stressed the relevance of definitions of socio-economic outcomes for the evaluation of the crisis, and their consequences to define interventions to fight socio-economic effects of the economic downturn. The adequacy of welfare policies to cope with social exclusion, especially during a crisis, has been called into question.